Extraction of Aloin from Aloe Vera plant and study its effect in Micronucleus Formation in Acute Lymphoid Leukemia - S. Alumairi, Sumaya; S. Shawkat, Muayad; A. Alaubydi, Mouruj (Iraqi Journal of Science, 2023)
Aloin extracted into alcohol-rich phase with high extraction efficiency,meanwhile majority polysaccharides, proteins, mineral substances and otherimpurities were extracted into salt-rich phase. Partitioning of AQs[Anthraquinones]is dependent on hydrophobic interaction, hydrogen bond interaction, and salting-outeffect in Aqueous tow –phase system [ATPS]. Aloin was partially purified by using1-propanol [NH4] 2SO4, the use of this solvent showed high efficiency 90.61%compared with other solvent [2-propanol and ethanol]. The concentration of aloindetected by HPLC technique, which reached to 91.84% as focus turns out that thereis compatibility between the sample and the standard in shape and retention timewhich reached [1.462] compared with the standard [1.465]. After the treatment ofblood leukemic patient cultures, three concentrations of aloin were used [100, 200and 400] μg/ml, the last concentration showed the ability to reduce the coefficient ofmicronucleus formation to [0.0062] micronucleus/cell, compared with non- treatedculture which reached to [0.0236] micronucleus/cell.